Kandungan Kalsium (C) dan Fospor (P) Silase Kombinasi Jerami Padi dan Daun Lamtoro Sebagai Pakan Ternak Ruminansia - Basri, Basri; Nurhaedah, Nurhaedah; Fitriani, Fitriani (bionature, 2019)
Abstract. The purpose of this study was to determine the calcium (Ca) content and phosphorus (p) silage combination of rice straw and lamtoro leaves as a good feed for ruminants. The Research Method used Completely Randomized Design (CRD) which consisted of 4 treatments and each treatment was repeated 3 times namely J0 = 100% Rice Straw + 0% Leucaena Leaves (Control), J1 = 60% Rice Straw + 40% Leucaena Leaves, J2 = 70% Rice Straw + 30% Leucaena Leaf and J3 = 80% Rice Straw + 20% Leucaena Leaf. The results showed that the combination of rice straw silage and lamtoro leaves showed that there was a very significant effect (P <0.01) on calcium (ca) and phosphorus (p) on rice straw and lamtoro leaves. The average value of calcium from highest to lowest is J1 (0.86%), J2 (0.82%), J3 (0.75%) and J0 (0.59%). The highest to lowest phosphorus values were J1 (0.29%), J2 (0.27%), J3 (0.23%) and J0 (0.19%). From the results of the study, it is known that the best treatment and can be recommended is J1 treatment consisting of 60% rice straw and 40% lamtoro leaves.Keywords: Rice Straw; Lamtoro Leaves; Silage; Calcium; Phosphor; Ruminant animals